Greek and Roman rewritings in "La virgen cabeza"’s "wretched baroque": A classical receptions perspective - Aprile, Guillermo Alberto (Tropelías: Review of Literary Theory and Comparative Literature, 2023)
The novel La virgen cabeza by Gabriela Cabezón Cámara explores the margins of Argentine society in different ways. Not only it depicts a story centered in socially excluded sectors, such as the inhabitants of slums (villas miseria) or the gender-dissident travestis, but also it accomplishes this by creating a language and literary form of its own, called “wretched baroque”. This paper uses the methodology of classical reception to analyze how several rewritings of the literature and culture of ancient Greece and Rome are integrated into the heterogeneous accumulation of discourses that characterizes the narrative universe of the novel.